Tradicionalni kazalci zvočne izolativnosti ne odražajo v celoti zvočnoizolacijske učinkovitosti pregrad - Ramšak, Mihael (Gradbeni vestnik, 2023)
The traditional way of evaluating sound insulation with a single number takes into account the poorer sound perception of lower frequencies, but does not take into account the spectrum of the noise source from which we want to insulate. For this reason, spectrum adaptation terms have been introduced, which make it possible to estimate the efficiency of the sound insulation performance of barriers for typical noise sources. The paper presents some typical examples that show the importance of the spectrum adaptation terms for the evaluation of the sound insulation performance of barriers, taking into account the noise sources spectra.
Keywords: kazalniki zvočne izolativnosti; korekcije za spektralno prilagoditev; odprti dostop; open access; sound insulation descriptors; sound insulation efficiency; spectrum adaptation terms; zvočnoizolacijska učinkovitost